(untitled) (Journal of the College of Basic Education, 2024)
Since the Safavid era, Persia witnessed reform ideas that were influenced by what was happening in the Ottoman Empire, and its transformations left traces in Persian society. The attempts of reform and modernization in the Ottoman Empire are very clear. The geographical aspect and the long borders between the Ottoman Empire and Persia contributed to the transmission of modern ideas and reformist tendencies to Persia, in addition to the role of diplomatic staff, merchants, and somemerchants, and some students and employees in that direction. The reform attempts in Persia had an impact on the course of Iranian history. Some of them did not succeed due to the opposition of some of the governmental and popular beneficiaries, on the other hand, they alerted the minds and reflected the extent of benefiting from the Ottoman or European reform to serve the Iranian society from which, especially the patriots, eventually entered into a struggle against the colonial powers and those who supported them in the country.